GENERAL CHARACTERISTICS OF PROBATION SUPERVISION IN CRIMINAL PROCEEDINGS OF THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The general characteristics and the emergence of probationary supervision in criminal proceedings are investigated. The versatility of such a phenomenon as probation is considered, which determines the plurality of scientific approaches to understanding its essence from the point of view of criminal law in the form of a measure of criminal law enforcement; penitentiary enforcement of probation supervision and control over persons conditionally early released from imprisonment and determined by the court of a correctional term for the period of probation supervision and from the point of view of criminal procedure law.
Keywords: probation, probation supervision, Criminal Procedure Law, Criminal legal im-pact, Correction of a person without isolation from society, Execution of probation supervision